ANALISIS PERHITUNGAN DAN PELAPORAN SECARA E-FILING PAJAK PENGHASILAN PASAL 21 ATAS GAJI PEGAWAI NEGERI SIPIL PADA KEMENTRIAN AGRARIA DAN TATA RUANG/BADAN PERTANAHAN NASIONAL KABUPATEN MALANG TAHUN 2015 - Tri Handari Wahyu Pancarani; Abdul Kodir Djaelani; Muhammad Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
AbstractThis study aims to determine whether the Ministy of Agricultural andSpatial/Malang District Land Board in calculating and reporter in the e-Filing ofincome Tax Article 21 of the salaries of civil servants in accordance whit theprovisions of the research is adescriptive study using quantitative approach PER-32/PJ/2015. The results obtained from the basic salary and all allowances are notin accordance whit the prevailing tax regulations, because the are difference inthe calculation of gross incame, mandatory dues employee becomes a deductionfrom gross income and the imposition of income tax rates section 21 on thesalaries of cipil e-Filing of of Income tax article 21 was reported by the taxpayerand are in accordance whit the applicable tax regulationsKeywords: Calculation, Reporting by e-Filing of Income Tax Article 21.